Pengembangan Model Pembelajaran Kesiapsiagaan Bencana Gempa Bumi Berbasis Simulasi Pada Sekolah Dasar di Lombok - Dodik Kariadi; Wasis Suprapto; Lussy Anggraeni; Farida Ariany; Yogi Setya Novanto (STKIP Singkawang, 2026)
The problem in this research is that the learning of Earthquake Disaster Preparedness based on simulation at schools in Lombok has not been optimal. In fact, the island of Lombok is an area with a high level of vulnerability to earthquakes. This is because one of them is the Flores Thrust which stretches from the eastern tip of the Flores Sea to the north of Bali. Thus in this study the main objective is to develop a model for the socialization of earthquake disaster preparedness through simulations in schools in Lombok. The research method used is a research and development approach. The results showed several results including; First, the results of preliminary research show that although the social studies learning for junior high schools in North Lombok has largely met the process standards seen from the learning administration, it is not specific in integrating the concept of earthquake preparedness. Second, the results of the research at the model practice test stage based on the results of qualitative analysis from the observation of students' preparedness skills showed that there was an increase in the quality of student preparedness in every meeting. Then quantitatively the results of the pretest-posttest after learning activities with the Simulation Based Earthquake Preparedness learning Model showed an increase in the value of students' preparedness against earthquakes. So with the development of an earthquake disaster preparedness learning model based on simulations, it is effective and efficient in order to improve school preparedness to face earthquake disasters in Lombok.